ERP and organizational change: a case study examining the implementation of accounting modules. Issue 3 (11th July 2016) - Hassan, Mostafa Kamal; Mouakket, Samar
Abstract : Purpose: The study aims at exploring the processes of implementing an enterprise resource planning (ERP) system in a public service organization operating in an emerging market economy, namely the United Arab Emirates (UAE). Design/methodology/approach: The study draws on Laughlin's (1991) model of organizational change in order to highlight how the introduction of an ERP system, particularly its accounting modules, disrupted the adopting organization's modes of thinking and its members' practices. It uses a case study methodology. Data collection methods included semi-structured interviews, documentary evidence, and personal observation. Findings: The case study findings show that despite implementation and customization problems, the organization's employees were forced to use the ERP system. The findings also highlight how the ERP system was acted upon to mobilize the organization's members toward a new era of Information Technology (IT). However, the misfit between pre- and post-ERP system accounting practices led some organizational members to form absorbing groups that questioned accounting-based ERP system organizational changes. The top management's persistent desire to adopt the ERP system through forcing the organization's employees to use the system's modules led the organization to undergo what Laughlin (1991) calls "colonization" organizational change. Research limitations/implications: The use of a case study methodology inherently limits the generalizability of the study's findings. The case study was carried out over a relatively short timeframe, namely 10 months. Therefore, the use of a longitudinal case study to examine accounting-based ERP organizational change is recommended. Practical implications: The study provides insights that can assist top management in formulating organizational change strategies. It also provides insights about emerging economies' regulatory particularities that influence ERP system implementation. Originality/value: The study is one of the first studies that utilizes Laughlin's (1991) model of organizational change to examine accounting-based ERP organizational change in an emerging market economy.